Effect of Intracanal Medicaments On MMP-9 And VIP Levels - SHAH, PALAK MAYUR; THANGAVELU, LAKSHMI (The journal of contemporary issues in business and government, 2021)
Root canal treatment is incomplete without usage of intra canal medicaments. They help in the reduction of bacterial count and its by-products, making canals clean and decreasing postoperative pains. The aim of this study was to evaluate the effect of calcium hydroxide (Ca [OH]2) and triple antibiotic paste on matrix metalloproteinase-9 (MMP-9) and vasoactive intestinal peptide (VIP). Thirty single rooted teeth with periapical lesions which require root canal treatment were randomly divided into 2 groups; Group 1- calcium hydroxide and Group 2- triple antibiotic paste. After access opening and working length determination, cleaning and shaping of the root canals were done and intracanal dressing was given. In the second appointment, medicaments were removed, and sampling was performed by collecting the interstitial fluid of the apical tissues by paper points to assess the MMP-9 and VIP levels. The MMP-9 and VIP levels were measured by the enzyme-linked immunosorbent assay. The concentration of MMP - 9 on Ca(OH)2 and TAP was 27.3pg/ml and 29.2pg/ml and VIP on Ca(OH)2 and TAP was 27.9pg/ml and 28.4pg/ml. There was no statistically significant difference between the intracanal medicament on the MMP-9 and VIP (p>0.05), proving that type of intracanal medicament does not influence MMP 9 and VIP levels.